A microwave cavity resonator sensor for water-in-oil measurements - Sharma, Prafull; Lao, Liyun; Falcone, Gioia (Elsevier, 2018)
Online monitoring of Water-Liquid Ratio (WLR) in multiphase flow is key in petroleum production, processing and transportation. The usual practice in the field is to manually collect offline samples for laboratory analysis, which delays data availability and prevents real time intervention and optimization. A highly accurate and robust sensing method is needed for online measurements in the lower end of WLR range (0%–5%), especially for fiscal metering and custody transfer of crude oil, as well as to ensure adequate flow assurance prevention and remedial solutions. This requires a highly sensitive sensing principle along with a highly precise measurement instrument, packaged together in a sufficiently robust manner for use in the field. In this paper, a new sensing principle is proposed, based on the open-ended microwave cavity resonator and near wall surface perturbation, for non-intrusive measurement of WLR. In the proposed concept, the electromagnetic fringe field of a cylindrical cavity resonator is used to probe the liquid near the pipe wall. Two of the cylindrical cavity resonance modes, TM010 and TM011 are energized for measurements and the shift in the resonance frequency is used to estimate liquid permittivity and the WLR. Electromagnetic simulations in the microwave frequency range of 4 GHz to 7 GHz are used for proof-of-concept and sensitivity studies. A sensor prototype is fabricated and its functionality demonstrated with flowing oil-water mixtures in the WLR range of 0–5%. The frequency range of the proposed sensors is 4.4–4.6 GHz and 6.1–6.6 GHz for modes TM010 and TM011, respectively. The TM011 mode shows much higher sensitivity (41.6 MHz/WLR) than the TM010 mode (3.8 MHz/WLR). The proposed sensor consists of a 20 mm high cylinder, with a diameter of 30 mm and Poly-Ether-Ether-Ketone (PEEK) filler. The non-intrusiveness of the sensor, along with the high sensitivity in the resonance shift, makes it attractive for practical applications.
Keywords: Microwave resonator sensor; Water-liquid ratio; Water cut; Multiphase flow measurement